Investigating Translation Strategies in the Indonesian Translation of Shopie's World: A Novel about the Histtory of Philosophy - Maharsi, Ista (English Education Department, Universitas Islam Indonesia, 2007)
Translating does not seem to be a trouble-free work. There are abundant tricks, strategies and adaptations to meet the need of being called 'sufficient' translation and thus it provides similar responses of the readers and brings about similar 'soul' of the original text. Translation works comprise many values and objectives of its author and the text itself. Not only is it a matter of transferring ideas or stories into other languages, but also a process of transferring culture, ideology, politics and social messages of the original text. This paper will discuss translation methods/strategies (the terms will be used interchangeably in this paper) that may be applied by the Indonesian translator in translating